2023
DOI: 10.3389/fcimb.2023.1193340
|View full text |Cite
|
Sign up to set email alerts
|

Potential interaction between the oral microbiota and COVID-19: a meta-analysis and bioinformatics prediction

Abstract: ObjectivesThe purpose of this study was to evaluate available evidence on the association between the human oral microbiota and coronavirus disease 2019 (COVID-19) and summarize relevant data obtained during the pandemic.MethodsWe searched EMBASE, PubMed, and the Cochrane Library for human studies published up to October 2022. The main outcomes of the study were the differences in the diversity (α and β) and composition of the oral microbiota at the phylum and genus levels between patients with laboratory-conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…In this meta-analysis, the Shannon index of COVID-19/influenza patients was reduced versus no COVID-19/influenza controls, which is consistent with the results of previous researches (17,18). Furthermore, when comparing COVID-19 patients with non-COVID-19 patients primarily presenting other respiratory symptoms such as flu and pneumonia, the Shannon index showed no significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…In this meta-analysis, the Shannon index of COVID-19/influenza patients was reduced versus no COVID-19/influenza controls, which is consistent with the results of previous researches (17,18). Furthermore, when comparing COVID-19 patients with non-COVID-19 patients primarily presenting other respiratory symptoms such as flu and pneumonia, the Shannon index showed no significant difference.…”
Section: Discussionsupporting
confidence: 90%
“…In a meta-analysis conducted by the team (authors), it was observed that additionally, COVID-19 disease significantly deepens the differences in the composition of the oral microbiota, especially in older people > 60 years of age compared to the group of patients < 60 years of age. These changes mainly involve a reduction in alpha diversity and an increase in the imbalance of the oral microbiome, which consequently leads to an increase in the level of opportunistic pathogens, including: Enterococcus, Enterobacter, Streptococcus, Veillonella, Prevotella Porphyromonas and Aggregatibacter 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Literature regarding the role of SARS-CoV-2 and bacteria co-infection in oral disease is even more scarce. A meta-analysis study by Tan et al demonstrates a drastic difference in the oral microbiome composition in COVID-19-positive patients compared to healthy controls, especially among the elderly [141]. Furthermore, a metagenomic analysis of COVID-19-positive patients revealed high reads of bacteria commonly implicated in oral disease (e.g., P. intermedia, Streptococci, Fusobacterium, Trepenome, and Veillonella) [110].…”
Section: Future Directionsmentioning
confidence: 99%